2009
DOI: 10.1007/s11205-008-9435-0
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict and Working Conditions in Western Europe

Abstract: Family and work, Work-life balance, Work conditions, European Social Survey, Job pressure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(164 citation statements)
references
References 16 publications
10
153
0
1
Order By: Relevance
“…Indeed, as Gallie and Russell (2009) found, studying male and female employees in couple households, longer working hours are associated with higher work-family conflict for both men and women. Studies have also found a clear association between work intensity/pressure and work-family conflict (Gallie and Russell, 2009;McGinnity and Russell, 2015).…”
Section: Notementioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, as Gallie and Russell (2009) found, studying male and female employees in couple households, longer working hours are associated with higher work-family conflict for both men and women. Studies have also found a clear association between work intensity/pressure and work-family conflict (Gallie and Russell, 2009;McGinnity and Russell, 2015).…”
Section: Notementioning
confidence: 85%
“…There is growing evidence that the experience of work-family conflict is more strongly influenced by working conditions than by family characteristics, especially hours of work, work pressure and scheduling (Gallie and Russell, 2009;Gronlund, 2007). Where this conflict is too great, women may exit the labour market or may not apply for promotions.…”
Section: Caring and Career Progressionmentioning
confidence: 99%
“…Job control is just one resource that can be deployed to reduce the negative effects of job demands (Bakker and Demerouti 2007). But the evidence is mixed as to which resources are effective under what conditions (Bakker and Geurts, 2001; Gallie and Russell, 2009;Steiber, 2009;Schieman and Young, 2010). It is common that people with high-status jobs experience high levels of conflict despite having access to resources that should help them to cope (Clarkberg and Moen, 2001;Gallie and Russell, 2009;McGinnity and Calvert, 2009;).…”
mentioning
confidence: 99%
“…What is perceived as a source of satisfactions by some workers can be viewed as an impediment by others. The differences concerning human resource policy are observed between men and women (Baral and Bhargava 2011;Gallie and Russell 2009), however, it seems that the variable is becoming less and less differentiating. Some studies indicate that there are clear differences between expectations in the range of desired elements of human resource policy at different organization levels (Moore 2007, Kasper et.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%